Environmental controls on carbon sequestration in a saline, boreal, peat-forming wetland in the Athabasca Oil Sands Region - Volik, Olena (University of Waterloo, 2018)
Saline boreal fens represent potential models for post-mining landscape reclamation in the Athabasca Oil Sands Region (AOSR) (Canada) where wetland construction is challenged by salinization. One of the key indicators of reclamation success is the accumulation of organic carbon within constructed fens, and a better understanding of the drivers of carbon sequestration in natural saline fens can be useful for advancing fen construction in this region. As such, this thesis aims to determine the main environmental controls on carbon uptake and its long-term storage in a saline boreal fen near Fort McMurray (Alberta, Canada) by: 1) reconstructing past salinity change; 2) determining relations between reconstructed salinity, hydrological conditions, vegetation and organic matter accumulation rates (OMAR) over the last ~100 years in open-water areas (ponds) within the fen; 3) investigating the effects of salinity, vegetation and hydrology on the long-term apparent rate of carbon accumulation (LARCA) within the peatland; and 4) assessing CO2 fluxes within the peatland and open-water areas. Past salinity change was investigated using paleolimnological analysis of sediment cores from three ponds situated within the fen. Salinity fluctuations were reconstructed using weighted-averaging transfer functions based on diatoms and an environmental dataset from 32 saline boreal ponds. Results reveal complex “precipitation – surface water – groundwater” interactions associated with differences in the hydrologic functioning of the studied ponds, and their connectivity with shallow groundwater aquifers and adjacent wetlands. Relationships between cumulative departure from mean precipitation (CDLM) and diatom-inferred (DI) salinity suggest that precipitation may control salinity both directly and indirectly. In ponds recharged predominantly by meteoric water, precipitation may govern salinity directly by dilution of salt content in water, so that increases in precipitation result in a salinity decline. In ponds situated within a ...